Prognostic significance of systemic inflammatory markers in esophageal cancer: Systematic review and meta‐analysis - Ishibashi, Yusuke; Tsujimoto, Hironori; Yaguchi, Yoshihisa; Kishi, Yoji; Ueno, Hideki (Annals of gastroenterological surgery, 2020)
Aim Impact of several immune‐inflammatory markers on long‐term outcome has been reported in various malignancies. The aim of the present study was to evaluate through a meta‐analysis the oncological outcome of immune‐inflammatory markers, such as neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and C‐reactive protein to albumin ratio (CAR) in esophageal cancer. Methods A systematic electronic search for relevant studies was carried out in PubMed, Cochrane library, Embase, and Google scholar. Meta‐analysis was done using hazard ratio (HR) and 95% confidence interval (CI) as effect measures. A systematic review and meta‐analysis were undertaken according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses protocol. P‐values <.01 were considered statistically significant. Results A total of 10 retrospective articles (n = 4551) were included in this study. Synthesized results showed that higher NLR and CAR were significantly associated with poor overall survival (HR 1.47, 95% CI = 1.32‐1.63, P < .00001) and HR 1.88, 95% CI = 1.28‐2.77, P < .001, respectively). On the contrary, PLR was not a prognostic factor in our analysis (HR 1.25, 95% CI = 1.01‐1.54, P < .01). Elevated NLR, PLR, and CAR were strongly associated with a higher T stage (HR 2.28, 95% CI = 1.67‐3.11; HR 1.57, 95% CI = 1.29‐1.90; HR 1.76, 95% CI = 1.16‐2.67, respectively). Begg’s funnel plots identified significant publication bias in NLR, but not in PLR and CAR. Conclusion NLR and CAR represent useful guides for the management of esophageal cancer, although publication bias should be considered. Further prospective studies are needed to confirm the results of the present study. Forest plot for the association between C‐reactive protein to albumin ratio (CAR) and overall survival of patients treated by surgery for esophageal cancer. Only three studies (n = 1033 patients) evaluated prognostic value of CAR. Cut‐off value of the included studies ranged from 0.085 to 0.5 (median, 0.22). Higher CAR was strongly associated with poorer survival versus lower CAR (HR 1.88, 95% CI = 1.28‐2.77, P = .001).